2022
DOI: 10.1002/cl2.1220
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Exploring the effect of case management in homelessness per components: A systematic review of effectiveness and implementation, with meta‐analysis and thematic synthesis

Abstract: This is the protocol for a Campbell review. The objectives are as follows: To carry out a mixed methods review to summarise current evidence relating to the components of case‐management interventions for people experiencing homelessness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Of note, due to our project's sample size and timeline, we were unable to gather data about CTI's effectiveness as part of this pilot initiative; as CTI is a well-established EBP (Susser et al, 1997 ; Herman et al, 2000 , 2011 ; Social Programs that Work, 2018 ; Ponka et al, 2020 ; Weightman et al, 2022 ), we relied heavily on existing data about practice effectiveness. However, the planned national implementation initiative will collect data about CTI's implementation and effectiveness by integrating qualitative and quantitative data.…”
Section: Acknowledgment Of Any Conceptual or Methodological Constraintsmentioning
confidence: 99%
“…Of note, due to our project's sample size and timeline, we were unable to gather data about CTI's effectiveness as part of this pilot initiative; as CTI is a well-established EBP (Susser et al, 1997 ; Herman et al, 2000 , 2011 ; Social Programs that Work, 2018 ; Ponka et al, 2020 ; Weightman et al, 2022 ), we relied heavily on existing data about practice effectiveness. However, the planned national implementation initiative will collect data about CTI's implementation and effectiveness by integrating qualitative and quantitative data.…”
Section: Acknowledgment Of Any Conceptual or Methodological Constraintsmentioning
confidence: 99%
“…Effectiveness studies were synthesised with a meta-analysis where feasible; while a framework synthesis was used to synthesise the factors that may impact on implementation. Methods followed those in the published protocol (Weightman, 2022) and findings are reported in line with the Campbell MECCIR reporting standards. 2…”
Section: Types Of Studiesmentioning
confidence: 99%
“…As per protocol (Weightman, 2022) it was agreed that, if a very large number of studies were identified, the review team would use a 'Best Fit Approach' based on a sample of studies using formal qualitative methods, and which are deemed most relevant (see Assessment of Findings).…”
Section: Implementation Studiesmentioning
confidence: 99%
“…Some case management models, such as assertive community treatment, involve multidisciplinary teams rather than single case managers. Other models, such as critical time intervention, explicitly recognise the importance of the right form of support being delivered at the right time, especially during periods of transition for clients (Weightman, Kelson et al 2022). The design of a systematic review of case management models identified the following as elements which can potentially be used to categorise models:…”
Section: Case Management Modelsmentioning
confidence: 99%